The linear 2-refined neutrosophic differential equations - Yaser Ahmad Alhasan; Issam Mohammed Abdallah Abdalaziz; Raja Abdullah Abdulfatah; Qusay Alhassan (Neutrosophic Sets and Systems)
In this paper, we studied the linear 2-refined neutrosophic differential equations and defined the homogeneous and non-homogeneous 2-refined neutrosophic differential equations. Also to presenting 2-refined neutrosophic differential equation of Bernoulli, which turns into a linear equation and thus facilitates its solution. Apart from talking about how to solve these equations and giving enough examples to support it.